The Increase of Business to Consumers (B2C) E-Commerce in Semarang, Indonesia (A Case of Lazada.co.id) - Mudiantono Mudiantono; Nadhissa Shadrina Zatalini (Forum Inovasi Bisnis dan Manajemen, 2019)
The online shopping nowadays has represented a significant escalation. A lot of e-commerce types have emerged in line with the changing of the way people shop from market place to market space. Lazada.co.id is one of e-commerce sites founded by Germany’s Rocket Internet, that now has become one of the most popular e-commerce sites in Indonesia. But, the popularity of Lazada.co.id should be reviewed due to the decrease of marketing performance during 2015-2016. It can also be seen from the decrease in the brand share of e-commerce Business to Consumer (B2C) values. The decrease of marketing performance is able to weaken Lazada.co.id site. This research is conducted to analyze factors that affect trust, buying interest, and transaction security in order to increase consumer buying decision of Lazada.co.id site in Semarang. By using data from 200 respondents who have made a purchase in Lazada.co.id throughout 2016, nine hypotheses are proposed through Structural Equation Model (SEM) analysis. The result of this research has shown that purchase decision is affected by trust. Consumer trust increases if the quality of product information given by the website is considerably good. Thus, it will form a consumer trust.